The Impact of Different Cover Crops, Mechanical Cultivation and Herbicide Treatment on The Soil Quality Variables and Yield in Apple (Malus domestica Borkh.) Orchard with a Coarse-Textured Soil - Doğan Işık; Zeynep Demir (Journal of Agricultural Sciences)
Effects of different cover crops on soil quality parameters and yield of an apple orchard located in Develi town of Kayseri province of Turkey were investigated in this study. Trifolium repens L. (TR), Festuca rubra subsp. rubra (FRR), Festuca arundinacea (FA), T. repens (40%) + F. rubra rubra (30%) + F. arundinacea (30%) mixture (TFF), Vicia villosa (VV) and Trifolium  eneghinianum (TM) were used as the cover crops in an apple orchard with sandy loam soil. Experiments also included plots mechanically cultivated (MC), herbicide treatment (HC) and control (C) plot without cover crops. Soil samples were taken from two different depths (0-20 and 20-40 cm) in each plot. Experiments were conducted in randomized complete blocks design with four replications. The cover crop treatments improved soil quality parameters like organic matter (OM), basal soil respiration, bulk density (BD), aggregate stability, saturated hydraulic conductivity (Ks), available water capacity compared to the soil of a nontreated control plot. Mean OM contents at 0-20 cm soil depth was ordered as; HC (0.56%)<C(0.62%)<MC(0.67%)<FRR(1.03%)<TM(1.06%)<TFF(1.09%)<FA(1.10%)<VV(1.34%)<TR(1.36%).The highest cover crop dry biomass mean was found in TFF treatment (45.5 ton ha-1), and the lowest was found in TM treatment (2.6 ton ha-1) in the apple orchard. While the highest mean apple yield was obtained from VV (23.9 ton ha-1) and TR (23.8 ton ha-1) treatments, the lowest mean apple yield (13.7 ton ha-1) was obtained from MC treatment. It was concluded based on the obtained findings that cover crops, especially Trifolium repens and Vicia villosa could be incorporated into cropping systems to improve soil quality and apple yield.